2002
DOI: 10.1007/s00421-002-0694-1
|View full text |Cite
|
Sign up to set email alerts
|

Standing and seated Wingate protocols in human cycling. A comparison of standard parameters

Abstract: While the Wingate test is traditionally administered with the restriction that the subject stay seated, competition cyclists generally rise out of the saddle when sprinting. The purpose of this investigation, therefore, was to determine whether the results of Wingate tests are different if they are obtained when the subject is in a seated compared to a standing position. A group of 12 male cyclists, competing at the college level, performed four 30 s Wingate tests over the course of 2 weeks. Two practice tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 13 publications
6
37
2
1
Order By: Relevance
“…team sprint, the kilometre race, or for the individual or team pursuit) where the results are often highly contested with close finishes. Our results are in line with Reiser et al [46] that have shown that the peak power output in the five first seconds of a Wingate test was higher in the standing compared with seated position (16.8 ± 0.9 vs. 15.7 ± 1.1 W/kg). The results of the present study are also in line with Bertucci et al [7] that have shown that during sprint tests in the field condition the power output was higher (p \ 0.05, ?15 %) and the time to peak power output shorter (p \ 0.05, -10 %) in the standing compared with the seated position.…”
Section: Effect Of the Riding Positionsupporting
confidence: 95%
“…team sprint, the kilometre race, or for the individual or team pursuit) where the results are often highly contested with close finishes. Our results are in line with Reiser et al [46] that have shown that the peak power output in the five first seconds of a Wingate test was higher in the standing compared with seated position (16.8 ± 0.9 vs. 15.7 ± 1.1 W/kg). The results of the present study are also in line with Bertucci et al [7] that have shown that during sprint tests in the field condition the power output was higher (p \ 0.05, ?15 %) and the time to peak power output shorter (p \ 0.05, -10 %) in the standing compared with the seated position.…”
Section: Effect Of the Riding Positionsupporting
confidence: 95%
“…Furthermore, maximum torque, which may be representative of bicycle-specific leg strength (Driss et al 2002) was slightly higher in the present study than previously reported values (Dorel et al 2005). The slightly higher values for torque and power data may in part be due to the fact that cyclists were allowed to stand out of the saddle during our trials, which is known to facilitate greater power and force production (Reiser et al 2002).…”
Section: Discussioncontrasting
confidence: 47%
“…Furthermore, the athletes must balance and control a moving bicycle while producing maximal power. Finally, sprint cyclists generally assume a standing position during the acceleration phase, which is known to allow greater power production (Reiser et al 2002). Consequently, the extent to which torque-and power-pedaling rate relationships derived in the laboratory accurately characterize the maximal capabilities during actual sprint cycling performance remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Standing to pedal increases power output 8% to 12% 20,21 and aerodynamic-drag area by 24%. 6 What if the road cyclist described had stood up to sprint?…”
Section: Sprint Performancementioning
confidence: 99%
“…6 Reiser et al 20 reported that subjects produced greater power (~8%) when performing a 30-second Wingate anaerobic test in the standing position. Davidson et al 21 have observed (in an abstract) a slightly greater (12%) increase in maximal cycling power during standing in a 3-second inertial-load test.…”
mentioning
confidence: 99%